Progress in parasitology - Mehlhorn, Heinz (Parasitology Research Monographs, 2011)
Parasites threaten the health of animals and humans alike. Especially in times of increasing globalization and global warming, parasites can enlarge their ?kingdom? by spreading. At the same time many of the existing medical products have become ineffective. As these products have been used for many decades, parasites have developed resistances, so that they have progressed in their fight for survival. Therefore it is obvious that humans must develop new methods to face these dangers.  Thus parasitological knowledge increases daily and must be formulated to be accessible for as many parasitologists (veterinarians, physicians, biologists) as possible. Therefore it is necessary that reviews reflecting the present status of the progress in many fields of research be published. Therefore this book, published on the occasion of the 50th anniversary of the German Society of Parasitology, compiles 18 reviews on recent ?hot topics,? including a new vaccine against malarial parasites; severe diseases with poor chances of treatment (cryptosporidiosis, coccidiosis, theileriosis); vectors (mosquitoes, ticks) and their transmission activities; and fish parasites, including molecular insights into the sex of parasites with a focus on the survival abilities that made them so dangerous. These chapters provide detailed information for researchers, as well as for teachers and students in parasitology.